2008
DOI: 10.2105/ajph.2007.117176
|View full text |Cite
|
Sign up to set email alerts
|

Physical Education and Academic Achievement in Elementary School: Data From the Early Childhood Longitudinal Study

Abstract: Among girls, higher amounts of physical education may be associated with an academic benefit. Physical education did not appear to negatively affect academic achievement in elementary school students. Concerns about adverse effects on achievement may not be legitimate reasons to limit physical education programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
184
2
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(211 citation statements)
references
References 29 publications
8
184
2
17
Order By: Relevance
“…Sibley & Etnier (2003) concluyen que la actividad física tiene un efecto positivo en los procesos cognitivos de los niños(as). Una de las relaciones estudiadas es entre rendimiento académico y tiempo dedicado a las clases de Educación Física (Carlson et al, 2008;Castelli et al, 2007;Eveland-Sayers, Farley, Fuller, Morgan & Caputo, 2009;Kin Isler, Asci & Kosar, 2002).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Sibley & Etnier (2003) concluyen que la actividad física tiene un efecto positivo en los procesos cognitivos de los niños(as). Una de las relaciones estudiadas es entre rendimiento académico y tiempo dedicado a las clases de Educación Física (Carlson et al, 2008;Castelli et al, 2007;Eveland-Sayers, Farley, Fuller, Morgan & Caputo, 2009;Kin Isler, Asci & Kosar, 2002).…”
Section: Discussionunclassified
“…Entre actividad física y rendimiento académico la única relación clara que se tiene es que el realizar actividad física no afecta negativamente el rendimiento académico (Carlson et al, 2008;Kirkendall, 1986). Una relación positiva se estableció con niños entre 8 y 11 años, en las materias de matemática y "Reading"; y la cantidad de horas acumuladas por semana en clases de Educación Física (Castelli, Hillman, Buck, & Erwin, 2007;Eveland-Sayers et al, 2009).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…7 Two similar studies conducted in USA found a positive relationship between PA and academic achievement. 8,9 Another research conducted in California, USA concluded that there was a consistent, positive and significant association between fitness scores and academic scores. 10 Dwyer t et al from Australia concluded that there was a positive association between cardiovascular fitness and academic achievement in children.…”
Section: Original Articlementioning
confidence: 99%
“…A growing body of research has indicated that PA is positively associated with academic performance outcomes in children, including classroom behaviour, cognitive skills and attitudes, and academic achievement [4][5][6]. Hence, the potential of classroom-based PA to increase PA and improve academic-related outcomes, such as classroom behaviour, cognitive performance, and academic achievement among children has gained interest among researchers and educators.…”
Section: Introductionmentioning
confidence: 99%